ANALISIS KOLERASI PENGETAHUAN DAN KECEMASAN IBU HAMIL DI MASA PANDEMI COVID-19 DI KLINIK BIDAN TITIN CIMANGIR KABUPATEN BOGOR - FITRIANI, DEWI; HARDIANTI, TITA; ARDI, NI BODRO; HANINGRUM, KATHERINA SYLVIA (Edu Dharma Journal :Jurnal penelitian dan pengabdian masyarakat, 2022)
ABSTRACTOne of the conditions that can change a person's physiological state is experienced by pregnant women, during the pregnancy process the body of pregnant women is more susceptible to infection. There were 5,564 Covid-19 cases in Indonesia until February 28, 2022. 448 cases. This condition can certainly cause an increase in stress and anxiety, especially in pregnant women, which can have an impact on their pregnancy status. The level of anxiety is certainly influenced by knowledge in each individual.  The purpose of the study was to determine the relationship between the level of knowledge and anxiety of pregnant women in the era of the Covid-19 pandemic at the titin cimangir midwife clinic, Bogor Regency. The method used in this study is a quantitative method using a cross sectional approach, the goal is to find out how independent variables and dependent variables are related, data are collected by distributing questionnaires. Samples were obtained by as many as 40 pregnant women at the midwife clinic in Cimangir, Bogor Regency. The results obtained were the age characteristics of the respondents obtained by the majority of pregnant women aged 25-35 years totaling 31 people (77.5%). More than half of pregnant women are at a low education level of 26 people (65%). The gestational age of respondents was mostly in the second trimester of 23 people (57.5%). A total of 28 respondents (70%) were out of work. 28 respondents (70%) with a low level of knowledge about Covid-19 and as many as 19 respondents experienced severe anxiety once (47.5%). The results of the statistical test obtained p value = 0.001 (alpa 0.05) then it can be concluded that there is a relationship between the level of knowledge and anxiety in pregnant women in the era of the covid-19 pandemic in the era of the covid-19 pandemic in the discipline of midwives titin cimangir bogor regency. ABSTRAKSalah satu kondisi yang dapat merubah keadaan fisiologis seseorang  diantara nya dialami oleh ibu hamil, selama proses kehamilan tubuh ibu hamil lebih rentan terkena infeksi. Kasus Covid-19 di Indonesia sendiri hingga pada tanggal  28 februari 2022 terdapat 5.564. 448 kasus. Kondisi ini tentunya dapat menyebabkan peningkatan stres dan kecemasan, terutama pada ibu hamil, yang dapat berdampak pada status kehamilannya. Tingkat rasa cemas tersebut tentunya dipengaruhi oleh pengetahuan pada setiap individu.  Tujuan dari penelitian untuk  mengetahui hubungan antara tingkat pengetahuan dan kecemasan ibu hamil di era pandemi Covid-19 di klinik bidan titin cimangir Kabupaten Bogor. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif dengan menggunakan pendekatan cross sectional, Tujuannya adalah untuk mengetahui bagaimana variabel independen dan variabel dependen terkait, data di kumpulkan dengan menyebarkan kuesioner. Sampel didapat sebanyak 40 orang ibu hamil di klinik bidan titin cimangir kabupaten bogor. Hasil yang diperoleh adalah karekteristik usia  responden didapatkan mayoritas ibu hamil berusia 25-35 tahun berjumlah 31 orang (77,5%). Lebih dari setengah ibu hamil berada pada tingkat Pendidikan rendah sebanyak 26 orang (65%). Usia kehamilan responden sebagian besar berada pada  trimester dua sebanyak 23 orang (57,5%). Sebanyak 28 responden (70%) tidak bekerja. 28 responden (70%) dengan tingkat pengetahuan yang rendah tentang Covid-19 dan sebanyak 19 responden mengalami kecemasan berat sekali (47,5%). Hasil uji statistic diperoleh p value = 0,001 (alpa 0,05) maka dapat disimpulkan bahwa ada hubungan antara tingkat pengetahuan dan kecemasan pada ibu hamil di era pandemi covid-19 diklinik bidan titin cimangir kabupaten bogor.